Implementasi Gerakan Belajar Dalam Meningkatkan Mutu Pembelajaran Bahasa Inggris di SMP Negeri 1 Baktiraja Kabupaten Humbang Hasundutan - Pittauli Sinambela; Romsina Siregar; Tetty A. Tambunan; Okti Marlindang Br. Pandiangan; Dosmauli Angelia Sianipar; Herman .; Mula Sigiro; Sabar Dumayanti Sihombing (LPPM UIKA Bogor, 2022)
Community service is an activity that aims to help certain communities in several activities without expecting any form of reward. This activity is carried out for 1 month in the school environment to assist teachers in teaching students who have fallen behind in learning. The lessons carried out include: Mathematics Lessons, English Lessons, Indonesian Language Lessons. This activity was carried out at SMP Negeri 1 Baktiraja from February 02 to February 26, 2022, Community Service activities were carried out after school at 14.00 – 15.30 WIB by making free tutoring. Students, schools, and students alike get many benefits from this program. Students get a lot of hands-on experience in the field, both during learning and also when planning programs with their peers. Meanwhile, the school admitted that it was greatly helped by the presence of students in teaching because during morning lessons many students were left behind in their learning so that by doing this free tutoring it could help students who were left behind in learning. Meanwhile, students get a lot of benefits in this program because students are helped in completing their assignments and assisted in learning that has been left behind. That way the students of SMP Negeri 1 Baktiraja feel happy with this program and can help them to more easily understand the material they don't understand.